Predicting Factors of Breast Self-Examination based on Health Belief Model and Locus of Control among Women Aged 20-50 Years - Afsaneh Sahraee; Azita Noroozi; Rahim Tahmasebi (حیات, 2013)
Background & Aim: Although breast self-examination (BSE) is no longer recommended for screening of breast cancer, its training and practicing is a gateway to health promotion and provides women with knowledge and attitudes that set the stage for clinical breast examination and mammography screening later in life. The aim of this study was to recognize predicting factors of the BSE based on the Health Belief Model (HBM) and the locus of control model among women aged 20-50 years old.